Effective institutional environment as a factor of stability of the economic system - I. A. Mankovsky (Вестник университета)
The current level of public administration involves the use of legal system as the only legitimate means of influencing participants in economic relations. By forming the legal system that acts as institutional environment for the national economy, the state determines the directions of economic development, sets incentives and restrictions for the development of certain sectors of the economy. The quality of the environment depends on the level of competence of government bodies and consideration in the process of creating formal rules which determine the directions of the economic development of objective economic laws. The purposes of the study are to elaborate criteria that the institutional environment should meet in order to act as a formal basis for sustainability of the economic system, and to justify the need to bring economics and law closer together in the process of economic analysis. The relevance of the study is due to the lack of a systemic connection between economic and legal sciences within the framework of economic analysis of the processes of development of the social system, which can have a negative impact on its reliability, and, as a consequence, on the effectiveness of the economic policy formulated by the state. The work establishes dependence of the quality of the institutional environment on the quality of the institutional structure, shows individual endogenous factors that negatively impact its effectiveness, and defines the directions for the formation of the institutional environment of the national economy, the implementation of which will achieve compliance with the goals and results of public administration of the economy. The study contributes to the development of institutionalism, promotes the creation of a unified institutional economic theory and conditions for its application for conducting an interdisciplinary economic analysis of various aspects of the development of Russian society as a complex social system.